BIMBINGAN ORANG TUA DENGAN DISIPLIN SISWA - Lina Novita; Anisa Agustina (Pedagonal : Jurnal Ilmiah Pendidikan, 2018)
ABSTRACTAThis study applied associative quantitative approach and correlational study on parents guidance as the free variable and students discipline as the bound variable. The main objective of this study is to investigate the strengths or weaknesses of the correlation between parents guidance and students discipline. The subject of this study was students of VB and VC classes from Ciampea 01 State Elementary School Bogor Regency, Even Semester, 2016/2017 Study Year, which were 90 students in total and 47 respondents were taken as samples. The validation of parents guidance and students discipline instruments was done through Microsoft Excel program with Pearson Product Moment formula. Meanwhile, instruments reliability was counted through Alpha Cronbach formula. The studys hypothesis instrument validation was done through a simple regression analysis with ? = -25,02 + 1,35X which means that the functional correlation is significant. In this study, each ascension of parents guidance unit will increase 1,35 unit of students discipline. The simple correlation trial states that (rxy) is 0,97 which means that the correlation between two variables is very strong, while the coefficient of determaination (r2) is 0,95 which means that parents guidance gives 95% contribution to students discipline. The rest 5% is determined by other factors. Based on the results of study above, it can be concluded that there is a positive correlation between parents guidance and students discipline.Keywords : Parents Guidance and Students Discipline